About the problem of the formation and development of the «genocide» concept in international legal science and practice - Adibayeva, A.K. (Karagandy University of the name of acad. E.A. Buketov, 2022)
The basic purpose of this article is to analyze the theoretical and practical aspects of the concept of «genocide» as an independent legal category in the context of the universal UN Convention of 1948 and beyond. The author, using also the decisions of specialized international judicial institutions, the doctrinal developments of scientists, and applying, together with them, general scientific and special research methods, formulates appropriate conclusions regarding the historical and modern understanding of the definition of this international socially dangerous act. It is substantiated that genocide, taking into account new forms and methods of its commission, is not only a crime against a person, a certain demographic community and humanity, but also against international law. The main conclusion is that, in view of the fact that law enforcement practice is ahead of the existing norms, the normative content of the definition of genocide and the closely related provisions of the Convention should be objectively interpreted in accordance with existing realities. In conclusion, as a result, attention is drawn to the fact that genocide, both as a concept and as a crime, requires further comprehensive scientific development, including within the framework of the development and systematization of knowledge in certain areas of Kazakhstani law.
«Геноцид» түсінігінің халықаралық-құқықтық ғылым мен тəжірибеде қалыптасуы мен дамуы туралы мəселеге қатысты
К вопросу о становлении и развитии понятия «геноцид» в международно-правовой науке и практике
Keywords: UN Convention; term; definition; concept; crime; historical facts; Nuremberg Tribunal; modern understanding; decisions of international tribunals